Q & A : Dialogue (Journal of School Administration Research and Development, 2016)
The ever-changing demands placed on school principals have necessitated the development of formal programs for improving the capacity of both existing school principals and those in the pipeline (i.e., assistant principals, vice-principals, and other aspiring school leaders). While there are several well-known development programs such as LEAD at Denver Public Schools and Broward County Public Schools in Florida, other school districts and educational institutions in other locales throughout the country have programs that have begun to emerge. In Dallas, Texas, Troy Mooney, Chief Academic Officer of Life Schools and Herbert O’Neil, Chief Talent Officer of Life Schools have developed a preparation guide and development program to meet the demanding needs of 21st-century school leaders.